Evidence for taping in overhead athlete shoulders: a systematic review - Turgut, E.; Can, E. N.; Demir, D.; Maenhout, A. (Research in Sports Medicine, 2023)
Taping is a popular approach and is often used as part of a multifactorial injury prevention programme for athletes. The aim of this study was to evaluate the current literature regarding the effects of shoulder taping in overhead athletes. Literature search was performed related to rotational range of motion (RoM), posterior shoulder tightness (PST), kinematics, muscular activity, acromiohumeral distance (AHD), proprioception, strength, and performance. Twenty studies were eligible. The majority of the applied taping methods were scapular and humeral head repositioning taping. Across all studies, there was limited to moderate evidence in favour of taping in overhead athletes with regard to rotational RoM, AHD, proprioception, and altering scapular kinematics, while taping did not enhance PST, muscular activity, shoulder strength, and performance. Therefore, the current evidence showed taping can alter some of the investigated factors that may have a therapeutic or preventive role. However, in the management of the athlete shoulder, taping-only approaches should not be focused on, and taping can be integrated in a more comprehensive approach for the overhead athletes.